2016
DOI: 10.1093/mnras/stw2247
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian analysis of two stellar populations in Galactic globular clusters– III. Analysis of 30 clusters

Abstract: We use Cycle 21 Hubble Space Telescope (HST) observations and HST archival ACS Treasury observations of 30 Galactic Globular Clusters to characterize two distinct stellar populations. A sophisticated Bayesian technique is employed to simultaneously sample the joint posterior distribution of age, distance, and extinction for each cluster, as well as unique helium values for two populations within each cluster and the relative proportion of those populations. We find the helium differences among the two populati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 65 publications
2
13
1
Order By: Relevance
“…Milone et al 2012;Piotto et al 2013;Milone 2015). Based on current samples, the fraction of second populations stars and their helium enrichment appears to vary significantly in different clusters (with 0.01 < ∆Y < 0.12) and may correlate with cluster mass (Wagner-Kaiser et al 2016;Milone et al 2017). The combination of first population stars and helium enhanced second population stars can help to explain the complex HB star morphologies observed in the Galactic globular clusters (e.g.…”
Section: Introductionmentioning
confidence: 85%
“…Milone et al 2012;Piotto et al 2013;Milone 2015). Based on current samples, the fraction of second populations stars and their helium enrichment appears to vary significantly in different clusters (with 0.01 < ∆Y < 0.12) and may correlate with cluster mass (Wagner-Kaiser et al 2016;Milone et al 2017). The combination of first population stars and helium enhanced second population stars can help to explain the complex HB star morphologies observed in the Galactic globular clusters (e.g.…”
Section: Introductionmentioning
confidence: 85%
“…Furthermore, other works based on HST data (Dalessandro et al 2014;Piotto et al 2015;Milone et al 2017) and high-resolution spectroscopy (Mucciarelli et al 2016) demonstrated that NGC 6362 hosts multiple stellar populations. Since NGC 6362 is one of the analyzed clusters in De Angeli et al (2005), Meissner & Weiss (2006), Marín-Franch et al (2009), Dotter et al (2010, Paust et al (2010), VandenBerg et al (2013 and Wagner-Kaiser et al (2016, it is a key comparison object for the present paper. It was identified as one of the oldest Galactic GCs by Marín-Franch et al (2009), Paust et al (2010), VandenBerg et al (2013 and Wagner-Kaiser et al (2016.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we are adopting that the 1G stars have primordial helium content (Y), which is consistent with the literature (Bastian & Lardo 2018). Wagner-Kaiser et al (2016) performed a bayesian isochrone fitting, in the context of MPs, for a sample of 30 GCs. Differently from the present work, they fitted the value of Y for the 1G stars, resulting in some cases in a high content of Y 1G ∼ 0.30.…”
Section: Age Difference ∆τmentioning
confidence: 99%
“…On the contrary, we are interested in finding if there is an age difference between the stellar populations. Even though our approach is similar to the one applied in Wagner-Kaiser et al (2016), the methods are based on different assumptions.…”
Section: Age Difference ∆τmentioning
confidence: 99%